2017
DOI: 10.1515/raon-2017-0059
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of tumor regression in locally advanced rectal cancer after preoperative radiochemotherapy

Abstract: BackgroundThe majority of rectal cancers are discovered in locally advanced forms (UICC stage II, III). Treatment consists of preoperative radiochemotherapy, followed by surgery 6–8 weeks later and finally by postoperative chemotherapy. The aim of this study was to find out if tumor regression affected long-term survival in patients with localy advanced rectal cancer, treated with neoadjuvant radiochemotherapy.Patients and methodsPatients with rectal cancer stage II or III, treated between 2006 and 2010, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…Pathologic complete response, determined by the lack of viable malignant cells in the surgically resected sample, is proposed as a pivotal prognostic criterion for long-term outcomes in LARC. 14 Patients achieving PCR after neoadjuvant treatment are less likely to have a local tumor recurrence and more likely to have a better survival outcome than patients with an incomplete response. 15 In a pooled analysis of survival outcomes for those attaining a PCR after preoperative chemoradiotherapy, 88.8% remained free of distant metastasis compared with 74.9% of patients without PCR at 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Pathologic complete response, determined by the lack of viable malignant cells in the surgically resected sample, is proposed as a pivotal prognostic criterion for long-term outcomes in LARC. 14 Patients achieving PCR after neoadjuvant treatment are less likely to have a local tumor recurrence and more likely to have a better survival outcome than patients with an incomplete response. 15 In a pooled analysis of survival outcomes for those attaining a PCR after preoperative chemoradiotherapy, 88.8% remained free of distant metastasis compared with 74.9% of patients without PCR at 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, Omejc and Potisek reported the rate of pCR to be 14.8%, with a five-year survival rates greater than 90% in those with pCR. 31 In a metaanalysis of 12 large studies, five-year survival rates in patients with pCR were reported as high as 90.2%. Likewise, higher survival rates were observed in patients with pCR.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that increasing pCR may help reduce the risk of recurrence and death. Although not sufficient to replace OS, pCR is considered an important prognostic parameter for the long-term outcome of LARC (46). Recent studies have shown that TNT increases the pCR of LARC, especially for high-risk patients, such as T4 and peripheral resection margin involvement.…”
Section: Discussionmentioning
confidence: 99%